Performance Evaluation of Turkish Ports: Integrated Fuzzy Entropy- Fuzzy MARCOS Analysis - Özlem Karadağ Albayrak (Verimlilik Dergisi)
Purpose: The aim of this study is to propose the Fuzzy Entropy based Fuzzy MARCOS method to solve the Multi Criteria Decision Making (MCDM) problem, which involves analyzing the performance of Turkish ports according to quantitative evaluation criteria. Methodology: The uncertainty of quantitative criteria is based on the different values they take at different time periods. To overcome this problem, in this study, the importance levels of the criteria were determined by the Fuzzy Entropy method. Then, 11 port alternatives with a share of over 1% in transportation in Turkish ports were ranked according to their performance using the Fuzzy Measurement of Alternatives and Ranking to Compromise Solution (MARCOS) method.Findings: According to the analysis results, the most important evaluation criterion used in the performance evaluation of container ports, that is, the criterion with the highest weight, is the “port area” criterion. The port with the highest performance value among the ports is Kocaeli port. This method can provide a more accurate evaluation of the performance level of ports and its use in the planning and effective use of port investments.Originality: This research fills the gap in the literature in three ways: (1) Evaluatee the application of triangular fuzzy numbers to the panel data, which will provide effective inferences about the performanse level of the selected ports, (2) Evaluated a weighting approach using Entropy method that takes into account the distances of triangular fuzzy numbers consisting of real numbers instead of linguistic expressions, (3) An Entropy-based MARCOS method is proposed for solving the Multi-Criteria Decision Making (MCDM) problem involving the performanse analysis of Turkish ports.